Cosmopolitan moment, cosmopolitan method
1 online resource.
Keywords: "In conversation, and in the company of a new generation of scholars working in the field, Nigel Rapport and Huon Wardle re-explore the terrain and meaning of cosmopolitan studies now. This book offers a new survey and theorisation of cosmopolitan research, a burgeoning topic responding to increasingly complex patterns of human interaction in world society. It considers the question of cosmopolitan methodology: what are the methods needed for, or elicited by, studying cosmopolitan situations? and how are we to remain faithful to the heteronomous human interiority and intentionality from which cosmopolitan moments are constructed? The volume focuses on the open-ended moment of ethnographic fieldwork that generates the concepts and methods needed to understand contemporary cosmopolitanization. The chapters cover a wide range of ethnographic situations and open up debate on what are the opportunities and responsibilities of a cosmopolitan anthropology in its exploration of human difference and commonality"--